When bins blur: Patient perspectives on categories of results from clinical whole genome sequencing. Issue 2 (3rd April 2017) - Jamal, Leila; Robinson, Jill O.; Christensen, Kurt D.; Blumenthal-Barby, Jennifer; Slashinski, Melody J.; Perry, Denise Lautenbach; Vassy, Jason L.; Wycliff, Julia; Green, Robert C.; McGuire, Amy L.
ABSTRACT: Background : Clinical genome and exome sequencing (CGES) is being used in an expanding range of clinical settings. Most approaches to offering patients choices about learning CGES results classify results according to expert definitions of clinical actionability. Little is known about how patients conceptualize different categories of CGES results.Methods : The MedSeq Project is a randomized controlled trial studying the use of whole-genome sequencing (WGS) in primary care and cardiology. We surveyed 202 patient-participants about different kinds of WGS results and conducted qualitative interviews with 49 of these participants. Interview data were analyzed both inductively and deductively using thematic content analysis.Results : Participants demonstrated high levels of study understanding and genetic literacy. A small majority of participants wanted to learn all of their WGS results ( n = 123, 61%). Qualitative data provided a deeper understanding of participants' perspectives about different types of WGS results. Participants did not have the same views about which WGS results would be actionable or upsetting to learn. They conceptualized variants of uncertain significance (VUS) in a variety of different ways. Many participants expressed optimism that the uncertainty associated with VUS results could be reduced over time.Conclusions : Proposals to determine which WGS/CGES results to disclose by soliciting patient preferences may fail to appreciate the complex ways patients think about disease and the information WGS/CGES can produce. Our findings challenge prevailing methods of facilitating patient choice and assessing the benefits and harms related to the return of WGS/CGES results, which mostly rely on expert definitions of clinical utility to categorize the kinds of results patients can learn.